Assessing the impact of HIV self-testing on diagnosis rates in vulnerable groups in belo horizonte, Brazil: A cross-sectional analysis - João Vitor Innecco Arêas; Gabriela Bragança Costa e Moreira; Gabriela Picchioni Baêta; João Vitor Levindo Coelho Novaes; Luísa Castro de Sousa Pires; Luara Isabela dos Santos (Public Health in Practice)
Background: In recent years, HIV self-testing (HIVST) has emerged as a promising approach to enhance accessibility and uptake of HIV testing, particularly among populations at high risk for sexually transmitted infections (STIs). Despite its potential benefits, the effectiveness, and challenges of HIVST warrant careful examination to inform public health strategies effectively. This study investigates the effectiveness and challenges of HIV self-testing (HIVST) in populations at high risk for sexually transmitted infections (STIs). Study design: Cross-sectional study. Methods: We employed questionnaires, HIVST, and standard tests for HIV, Hepatitis C, and Syphilis, in patients exhibiting STI risk behaviors in Belo Horizonte, Brazil, between August and November of 2019. Results: We engaged 125 individuals, median age of 33.5 years, with most participants (61 %) deviating significantly during self-testing. Despite this, HIVST was generally perceived as user-friendly. From the perspective of health professionals, there was 100 % agreement between HIVST and the gold standard HIV testing results. Notably, among those seeking solely HIV testing, 19.2 % tested positive for Syphilis, and 4.8 % for Hepatitis C. Only a minority (4.8 %) were aware of the HIV window period. Conclusion: While HIVST presents benefits, the evidence does not yet support its widespread adoption as a standalone public health policy. Moreover, exclusive reliance on HIVST might mask the prevalence of other STIs. We advocate for a holistic approach to HIV and STI testing, incorporating education, counseling, and comprehensive healthcare access in public health initiatives.